Escalonamento de sistemas de produção híbridos usando uma rede de Petri P-temporal T-temporizada com mecanismo de retrocesso inteligente - Moraes Junior, Clarimundo Machado (2000)
The objective of this work is to deal the scheduling problem of the batch systems, with cyclic feeding policy. based on the representation of the system constraints using a p-time t-timed Petri net model and on a t.oken player algorithm with a intelligent backtrack mechanism to find a feasible sequence consistent with the set of constraints. The p-time t-timed Petri net is more general than an event graphs, it allows on the hand to separate the production routes constraints and the resource allocation constraints and on the other hand to modelize the operation durations of treatament of the batch as- sociated with the places and ths operation durations of transference of the batch associates with the transitions. Furthermore. the backtrack mechanism used in this work not is sistematic but intelligent in accord with analyse of the net’s present State.